Compassionate leadership sustaining wisdom, humanity and presence in health and social care - West, Michael A. 1951- (The Swirling Leaf Press, 2021)
Those who work in health and social care give inspiring support for the health, happiness and well-being of all - communities, societies and nations. Yet their workplaces often harm their own health and well-being, affecting care quality, motivation, patient satisfaction and corroding cultures of compassion.In these pages, an evidence-based approach to transforming the leadership and cultures of health and social care teams and organisations is described. Practical, powerful and compelling, it describes a strategy based on the core human value of compassion, showing that by sustaining that value in health and social care, we can cultivate wisdom, humanity, presence and high-quality in health and care services. Supplemented with practical resources, case examples and searching questions for discussion, it offers a simple, radical and powerfully effective strategy for change. It is a call for leaders to nurture compassion within themselves and across health and social care institutions, to support healthier and happier institutions and communities. It challenges leaders at every level to have the courage and authenticity to embody compassion in their leadership now and for the long-term future
Keywords: Gesundheitswesen; Sozialeinrichtung; Sozialarbeit; Führungsstil; Health services administration; Delivery of Health Care; Leadership; Compassion; Empathy; Empathie; empathy; Medical care